Effect of Different Sources of Nitrogen on Kachari (Cucumis melo) Performance in the Arid Region - Jatav, M K; Sharma, B D; Ssmsfis, D K; Meena, S R (Annals of Arid Zone, 2016)
The field experiment was conducted at Central Institute of Arid Horticulture (CIAH), research farm with popular kachari cultivars AHK119 during 2015 in the kharif season to investigate the effect of different sources of nitrogen on kachari performance. Different source of N showed significant effect on growth attributes, as well as yield and nutrients uptake by kachari. 80 kg N ha-1 through neem coated urea as spilt application proved to be more effective in terms of growth attributes, kachari yield, nutrients uptake and recoveries. Neem coated urea application was more superior than calcium nitrate and urea.